2020
DOI: 10.1016/j.btre.2020.e00515
|View full text |Cite
|
Sign up to set email alerts
|

The role of rice husk biochar addition in anaerobic digestion for sweet sorghum under high loading condition

Abstract: Highlights Rick husk biochar addition mitigated the pH decrease during high load sorghum AD. 20 g/L biochar addition reduced the peak total VFA by 375 mg/L at F/M ratio of 1.2. Maximum methane production rate was increased by 25 % with 15 g/L biochar addition. Lag phase time was decreased by 45 % with 15 g/L biochar addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 26 publications
0
15
1
1
Order By: Relevance
“…At least in the short term, no significant differences between the treatments were detected (p = 0.637). This is surprising and contradicts previous reports of an accelerated degradation of fibrous biomass [66], even though the authors suggested an optimum biochar concentration of 15 g L -1 , which is approximately six times and three times higher than seen for the low and the high concentration in this study, respectively. This may at least partially explain the divergence of both studies; however, more research is needed to investigate the degradation of lignocellulose-rich biomass at 45°C, since it represents one of the major drawbacks of AD when treating agricultural residues.…”
Section: Gas Measurement and Physico-chemical Analysiscontrasting
confidence: 99%
“…At least in the short term, no significant differences between the treatments were detected (p = 0.637). This is surprising and contradicts previous reports of an accelerated degradation of fibrous biomass [66], even though the authors suggested an optimum biochar concentration of 15 g L -1 , which is approximately six times and three times higher than seen for the low and the high concentration in this study, respectively. This may at least partially explain the divergence of both studies; however, more research is needed to investigate the degradation of lignocellulose-rich biomass at 45°C, since it represents one of the major drawbacks of AD when treating agricultural residues.…”
Section: Gas Measurement and Physico-chemical Analysiscontrasting
confidence: 99%
“…First, the lower pH value caused by the formation of volatile fatty acids can be offset by some functional groups in the biochar, where the amine group adsorbs hydronium ion and acts as an electron acceptor media. Biochar's exceptional buffering capability against the formation of volatile fatty acids in anaerobic digesters operating at a higher organic loading rate was previously reported (Ma et al 2020 ). Second, the inorganic metals contained in biochar, such as calcium, magnesium, potassium, sodium, silicon, iron, aluminium, and sulphur, can contribute to the biochar's alkalinity characteristics (Zhang et al 2018b ).…”
Section: Anaerobic Digestionmentioning
confidence: 68%
“…For example, it was reported that the addition of 10 g L −1 of substrate biochar to thermophilic semi-continuous anaerobic digestion of food waste improved the pH value from 7.7 to 8.2 and mitigated the formation of total volatile fatty acids due to its buffering capacity (Lim et al 2020 ). Similarly, a decreased lag phase of up to 44% and a 25% increase in methane productivity were reported as a result of the buffering effect of the 15 g L −1 addition (Ma et al 2020 ).…”
Section: Anaerobic Digestionmentioning
confidence: 80%
See 1 more Smart Citation
“…In fact, the continuous increase in the VFA: TAC ratio from 0.67 to 0.89 revealed that R2 was overloaded, marking the process failure of the digesters fed with mixed food waste and agricultural residue, at an OLR of 4 kg VS/m 3 •d. On the other hand, relatively stable performance of R3 was observed under the same experimental conditions with a VFAs concentration of 3115 mg/L, and a total alkalinity of about 5840 mg CaCO 3 /L, indicating that the system was not inhibited by acidification, even if the VFA: TAC ratio overstepped the upper bound of the overloading value by attaining 0.53 [62]. In the same context, Ma et al, (2020) reported that accumulated acids were readily converted to biogas in the presence of biochar as an additive because such a buffering agent might be efficient in terms of reducing VFA accumulation by boosting the direct interspecies electron transfer (DIET) functions between acidogenesis and methanogenesis microorganisms [63].…”
Section: Effect Ofmentioning
confidence: 84%